How is musculoskeletal spinal content taught in entry-level doctor of physical therapy programs? A mixed-methods study. - Kirker, Kaitlin; Young, Jodi L.; Masaracchio, Michael (Physiotherapy Theory & Practice, 2026)
Introduction: One explanation for inconsistent adherence to evidence-based recommendations in the management of spinal pain may be related to the physical therapist's philosophical approach, which is likely initiated during their entry-level education. A significant gap exists in the systematic study of physical therapist education, prompting recent calls for meaningful reform within the field. The aims of this study were to identify the unique number of orthopedic philosophical approaches to teaching musculoskeletal spine content across DPT curricula and to explore the beliefs of faculty members regarding musculoskeletal spine education. Methods: This was a mixed methods research study with an electronic survey including both quantitative and qualitative questions, followed by an optional semi-structured virtual interview. Faculty members teaching musculoskeletal spine content in CAPTE-accredited DPT programs (n = 252) were invited to participate. Survey questions included demographics, orthopedic philosophical approaches, and methods of curricular design for teaching musculoskeletal spine content. The semi-structured interview explored themes in curricular design and approach to musculoskeletal spine education. Quantitative data was analyzed using descriptive statistics. Qualitative data was analyzed using grounded theory procedures to explore themes. A convergent design with a merging approach was used for data integration. Results: Fifty-four faculty completed the survey, with 12 interviewed. A variety of orthopedic philosophical approaches were used, with all identified approaches implemented to some degree across DPT programs. Participants indicated that they do not implement one primary approach. Three overarching themes were revealed: Pragmatic Teaching and Learning Effectiveness, Curricular Integration for Adaptive Practice, and Clinical Applicability. Conclusion: Findings reveal underlying themes that may explain the variability in how musculoskeletal spine content is taught in DPT programs. Insights into the current educational atmosphere have the potential to inform curricular refinement to ensure entry-level education upholds its obligation to produce competent practitioners prepared to meet the needs of society.